Surface Tension Gradient as Additional Driving Force for Grain Boundary Diffusion. Equilibrium and Non-Equilibrium Cases - Bokstein, B.; Rodin, A. (Металлофизика и новейшие технологии, 2013)
Classic Fisher model of grain-boundary diffusion with leakage into bulk is generalized by consideration of the surface-tension change along the grain boundary.